A Reflection of Man as a Social Being in Human Philosophical Thought - Milton T. Pardosi (Jurnal Indonesia Sosial Teknologi, 2024)
This research reflects on man as a social being and the relationship of humans as a social being with philosophy. The method used in this research is qualitative. The researcher will use this type of research description based on existing data or facts obtained in the field. The researcher analyses library data to produce a new understanding of human existence as a social being associated with the nature of humans as social beings in the thought of Human Philosophy.  The results of the study are that human beings, as social beings, are bound to norms or rules.  Man is open to the existence of others, shares the world with others, and is responsible for society.  The nature of man as a social being is: Homo Religious; Homo Sapiens; Homo Viator; Homo Creator; Homo Homini Lupus; Homo Homini Socius. The relationship of man as a social being with philosophy can be understood through the meaning of philosophy first